Liquid phase nitration of benzene to nitrobenzene using a mesoporous MoO3/Nb2O5 nanocatalyst - Kalbande, Pavan Narayan; Swapna, Bhattu; Sudarsanam, Putla; Umbarkar, Shubhangi B. (Catalysis Letters, 2025)
This work reports the synthesis of a mesoporous MoO3/Nb2O5 catalyst by a facile co-precipitation method for the liquid phase nitration of benzene to nitrobenzene, which is a vital industrial reaction. Pristine Nb2O5 and MoO3/Nb2O5 nanocatalysts were characterized using various techniques, including powder XRD, N-2 adsorption-desorption, Raman, SEM/TEM, pyridine FT-IR, and XPS. The MoO3/Nb2O5 catalyst (10 wt% MoO3 with respect to Nb2O5) showed uniform dispersion of Mo and Nb species, higher amount of oxygen vacancies, and more Br & oslash;nsted acid sites, resulting in a 90% yield of nitrobenzene. In contrast, only 35 and 58% yields were obtained in the case of commercial Nb2O5 and nanosized Nb2O5, respectively. The liquid phase nitration of benzene was carried out using commercial 65% HNO3 as a nitrating agent without sulfuric acid. The mesoporous MoO3/Nb2O5 catalyst is structurally stable, as confirmed by the characterization of the spent catalyst. However, a gradual decrease in the yield of nitrobenzene was observed, which could be due to the leaching of MoO3 species from the catalyst surface.
Keywords: Benzene nitration; Bronsted acid sites; Mesoporous MoO3/Nb2O5 Catalyst; nitrobenzene; Uniform metal dispersion